Sustainable UAO: Paving the Way Forward in the Rise of Sustainability as Institutional Ethos - Gandini, Mario A.; Cardona, Jesus D.; Amar, Luis F. (Universitas Diponegoro, 2024)
In response to the pressing global environmental crisis precipitated by the transgression of planetary boundaries due to human activity, the Universidad Autónoma de Occidente (UAO) has made a steadfast commitment to the development of theories, strategies, and practices concerning sustainability since the late 1990s. Through the establishment of both undergraduate and graduate programs, as well as research projects and the Sustainable Campus initiative, UAO has laid the groundwork for national and international recognition in addressing sustainability. Acknowledging the progress made and the historical context, UAO recognizes that the time has come to take a significant quality step towards a more comprehensive and dedicated commitment. This step involves elevating sustainability to the status of institutional ethos. This entails ensuring that the principles of sustainability are prominently and explicitly integrated into the core functions of the university, including teaching, research, and social outreach. This work looks at the journey thus far and, more importantly, charts the course for the future in the elevation of sustainability as institutional ethos. It highlights the key milestones achieved over the past two decades while identifying the most significant challenges and barriers that the university must confront and overcome in the near future to fully embody this ethos. By doing so, UAO aims to realize its ambitious goal of becoming a truly sustainable institution.